Operationalizing 17α-Hydroxyprogesterone Caproate to Prevent Recurrent Preterm Birth: Definitions, Barriers, and Next Steps. Issue 6 (December 2016) - Stringer, Elizabeth M.; Vladutiu, Catherine J.; Batra, Priya; Stringer, Jeffrey S. A.; Menard, M. Kathryn
Abstract : Each year in the United States, more than 500, 000 neonates are born before 37 weeks of gestation. Women who have experienced a previous preterm birth are at high risk of recurrence. A weekly prenatal injection of 17α-hydroxyprogesterone caproate decreases the risk of recurrent preterm birth and is recommended from as early as 16 weeks of gestation in women carrying singleton pregnancies who have a history of spontaneous singleton preterm birth. A commonly used metric for public health program effectiveness is population coverage of an intervention. In the case of 17α-hydroxyprogesterone caproate, population coverage can be defined as the proportion of women who are eligible for 17α-hydroxyprogesterone caproate (ie, previous pregnancy complicated by spontaneous singleton preterm birth) who actually receive the intervention. To receive a full course of 17α-hydroxyprogesterone caproate, women must negotiate a complex series of steps that includes presenting early for prenatal care, being identified as eligible for 17α-hydroxyprogesterone caproate, being offered 17α-hydroxyprogesterone caproate, accepting 17α-hydroxyprogesterone caproate, and adhering to the weekly 17α-hydroxyprogesterone caproate dose schedule. We describe this series of steps as well potential solutions to increase 17α-hydroxyprogesterone caproate coverage. Abstract : 17α-hydroxyprogestone decreases the risk recurrent preterm birth, but its widespread use has foundered because of a complex set of patient- and system-level factors that are reviewed in this article.